PERNIKAHAN DAN KAITANNYA DENGAN PENDIDIKAN ANAK MENURUT AJARAN ISLAM - Frimayanti, Ade Imelda (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2014)
Marriage is not only aiming to channel the biological potential of Allah given to men in a way that is good and right, as well as to obtain good and clear descent nasab as well as maintenance of effort and approach to Allah SWT. From this marriage has a strong link in the education of children. Education of children begins before the wedding is to look for a husband and wife are devout candidate will be able to provide a good education for their children. Only then will emerge from the marriage education responsibilities to their children either in the womb, when born into the world, and until he was an adult.